Kolaborasi Guru dan Orang Tua Dalam Meningkatkan Kedisiplinan Siswa Madrasah Ibtidaiyah - Jamel, Jamel; Tanjung, Siti Hajar (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study explores the collaboration between teachers and parents in enhancing student discipline at MIS Al-Washliyah Labubahan Batu Utara. Using a qualitative research design with a phenomenological approach, the research examines the forms of collaboration and the challenges faced in this context. Data was collected through observations, interviews, and document analysis, involving teachers, parents, and the school principal. The results show that the collaboration focuses on both academic and non-academic activities, such as regular meetings to discuss academic progress and student discipline. However, challenges such as time constraints, differences in understanding of discipline, and social-economic factors were identified as obstacles. The study emphasizes the importance of effective communication and mutual understanding between teachers and parents to foster student discipline. The findings offer insights for improving collaboration in similar educational settings, especially in rural and religious-based schools. This research contributes to understanding the dynamics of teacher-parent collaboration in enhancing student behavior and discipline.